Mining project's economic impact on local communities, as a social determinant of health: A documentary analysis of environmental impact statements - Hresc, Jessica; Riley, Emily; Harris, Patrick (Environmental impact assessment review, 2018)
Australian mining developments cause indirect economic impacts on nearby communities leading to poor health and wellbeing of local residents. Economic instability is a recognised social determinant of health (SDoH); however, SDoHs are rarely considered adequately in Environmental Impact Assessments (EIAs). This research aimed to determine the extent economic impacts as a SDoH are considered in three Environmental Impact Statements (EISs) of mining projects in the New South Wales, Australia. We adopted an exploratory case study design following Yin (2012). Three cases in New South Wales, Australia, were purposively sampled as being of concern to the local community who had sought legal advice about the content of the EIS (although not necessarily for health reasons). Two were open cut mines: Watermark located in the Liverpool Plains and Warkworth Continuation in the Hunter Valley Region. The third is a comparative case – the underground Mandalong Southern Extension located in Lake Macquarie. We adapted a health-focused EIA coding framework to investigate how economic indicators as SDoH were explicitly mentioned in EISs and applied this to the three cases. Economic indicators as SDoH were rarely considered. There was a greater focus on population characteristics rather than the potential economic impacts of the mining projects on the communities. Causal association of economic determinants and health outcomes were insufficiently reported compared to best practice, and health data were not used to inform assessments. Despite two EISs – Warkworth Continuation and Watermark – associating some economic indicators to health outcomes, impacts were not adequately discussed when compared to the known literature on economic impacts of mines. Our findings show that the three EISs were inadequately utilised to determine economic impacts of mining projects on the health and wellbeing of local communities. The evidence base linking economic impacts of mines to health is underdeveloped, which compromises assessing the quality of economic coverage in EISs. EIA scoping should enable sufficient inclusion of broader determinants of health using appropriate methodology, and the economic-focused content of EISs should be subject to rigorous peer-review process to fully inform government approvals for projects. Our methods lend themselves to research in other contexts to investigate the quality of EIAs.